Inklusivitas Ramadhan: Dialog Lintas Agama di Pura Segara Suci dan Pendampingan Psikososial Pascabencana Padasari - Fitriyanto Fitriyanto; Ibnu Sulaiman (Universitas Muhammadiyah Ponorogo, 2026)
Post-disaster crises often trigger psychological paralysis and social polarization due to limited inclusive dialogue spaces, even during Ramadan, which should strengthen interfaith solidarity. This study aims to analyze the actualization of religious moderation through inclusive spatial politics and its correlation with psychosocial assistance for vulnerable groups and survivors' resilience. This study utilizes a descriptive qualitative multi-locus design with a Participatory Action Research (PAR) approach and the Participatory Action and Learning System (PALS) framework. Intensive research was conducted from February to March 2026 at Pura Segara Suci in Tegal City and Padasari Village, Tegal Regency. Data from purposively selected informants including academics, Hindu devotees, BNPB authorities, student delegates (HMPS PPKn, BEM FKIP, Civic Kolaborasik), and child survivors were gathered via interviews, emic observation, and documentation, validated through triangulation, and analyzed descriptively-narratively. The results show that deconstructing Pura Segara Suci's function into inclusive spatial politics effectively dissolves rigid dogmatism and theological prejudice based on Pawongan and Tat Twam Asi values. This action-dialogue success was replicated in psychosocial assistance grounded in Psychological First Aid (PFA) and Ethics of Care to heal child survivors' trauma. This collaborative student intervention successfully triggered behavioral transformation and civic values internalization, awakening the community's collective efficacy to transform from passive victims into active survivals for post-disaster social justice.